Spatial assessment of nighttime anthropization in the Comoé National Park in Côte d’Ivoira (West Africa) - Sylla Gaoussou; Coulibaly Talnan Jean Honoré; Coulibaly Naga; Kouadio Koffi Claude Alain; Coulibaly Houebagnon Saint Jean Patrick; Cissé Souleymane; Sie Kambiré (Ekológia (Bratislava), 2023)
Protected areas play a crucial role in preserving biological diversity, providing ecosystem services, and regulating hydroclimatic processes. However, the environmental balance of these areas is increasingly under threat due to rapid population growth, high demand for natural resources, and the effects of global warming. To address this, sustainable management of protected areas is essential. This study aims to develop a methodology for monitoring and assessing levels of nocturnal anthropogenic aggression in the Comoé National Park (CNP) in Côte d’Ivoire. By using geospatial data from the Day/Night Band of the Visible Infrared Imaging Radiometer Suite (VIIRS/DNB), the study characterizes the nocturnal anthropization of CNP through the use of several indices. First, light reflectance density is used to identify nighttime light emission foci. Second, the lighted area density index (LADI) is employed to understand the nature of nocturnal activities taking place within CNP, as indicated by artificial light at night (ALAN). Finally, the light intensity index (LII) is used to evaluate the degree of influence of nocturnal anthropogenic activities on biodiversity. The study also found important activities through LADI and observed a high level of light pollution in CNP. Ultimately, the findings of this study indicate that there is a significant level of nocturnal anthropization within CNP, highlighting the need for effective management and conservation efforts in the area.